2022
DOI: 10.3389/fnins.2022.721987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcranial Direct Current Stimulation on the Mismatch Negativity Features of Deviated Stimuli in Children With Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a devastating mental disorder in children. Currently, there is no effective treatment for ASD. Transcranial direct current stimulation (tDCS), which is a non-invasive brain stimulation neuromodulation technology, is a promising method for the treatment of ASD. However, the manner in which tDCS changes the electrophysiological process in the brain is still unclear. In this study, we used tDCS to stimulate the dorsolateral prefrontal cortex area of children with ASD (one group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…DLPFC was the most often-targeted region (Fig. 3b,d) and here, anodal tDCS over the left dlPFC (in 7 out of 11 studies) [53][54][55][70][71][72][73] was the most often applied protocol in ASD. In one study 74 , a significant improving effect of bilateral anodal dlPFC tDCS was observed on overall behavioral symptoms.…”
Section: Autism Spectrum Disordermentioning
confidence: 66%
See 2 more Smart Citations
“…DLPFC was the most often-targeted region (Fig. 3b,d) and here, anodal tDCS over the left dlPFC (in 7 out of 11 studies) [53][54][55][70][71][72][73] was the most often applied protocol in ASD. In one study 74 , a significant improving effect of bilateral anodal dlPFC tDCS was observed on overall behavioral symptoms.…”
Section: Autism Spectrum Disordermentioning
confidence: 66%
“…The risk of bias for each tDCS study in ASD is reported in Figure 2b 53 , the source of other bias is related to comorbidity of patients. Most of the enrolled patients were accompanied by degrees of comorbidities including anxiety disorder, ADHD, and attenuated psychosis syndrome.…”
Section: Tdcs Studies In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…and here, anodal tDCS over the left dlPFC (in 7 out of 11 studies) (Amatachaya et al, 2014;Amatachaya et al, 2015;Han et al, 2022;Kang et al, 2018;Qiu et al, 2021;Sun et al, 2022;Toscano et al, 2019) was the most often applied protocol in ASD. In one study (Hadoush et al, 2020) on behavioral symptoms (Toscano et al, 2019), and anodal stimulation over the primary motor cortex on motor skill training in children with ASD (Mahmoodifar & Sotoodeh, 2020).…”
Section: Autism Spectrum Disordermentioning
confidence: 84%
“…The risk of bias for each tDCS study in ASD is reported in Figure 2b. In Sun et al (2022), the source of the other bias is related to comorbidity of patients. Most of the enrolled patients were accompanied by degrees of comorbidities including anxiety disorder, ADHD, and attenuated psychosis syndrome.…”
Section: Tdcs Studies In Asdmentioning
confidence: 99%